Letters of Samuel Taylor Coleridge, Vol. 1 (of 2) - Coleridge, Samuel Taylor, 1772-1834; Coleridge, Ernest Hartley, 1846-1920 (Salt Lake City, UT : Project Gutenberg, 2014)
"Letters of Samuel Taylor Coleridge, Vol. 1 (of 2)" by Samuel Taylor Coleridge is a collection of personal letters written in the late 18th and early 19th centuries. This volume showcases the correspondence of the renowned poet and philosopher, providing insights into his life experiences, relationships, and reflections during his formative years. The letters frequently focus on Coleridge$1 (Bs thoughts about literature, his family background, and his evolving identity, as well as his interactions with friends and contemporaries like Thomas Poole and Robert Southey. The opening of the collection introduces readers to Coleridge's life story, beginning with his childhood in Devonshire. Coleridge expresses a desire to recount his biography honestly, noting the mix of virtues and flaws that shaped him. He shares anecdotes about his family, including his father's struggles, his early education, and the complexities of sibling relationships. This reflective and engaging introduction effectively sets the tone for the letters that follow, highlighting Coleridge's introspective nature and his earnest desire to connect with his readers while illustrating the formative influences on his poetic career. (This is an automatically generated summary.)s
Release date is 2014-01-01
E-text prepared by the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Poets, English -- 19th century -- Correspondence; Coleridge, Samuel Taylor, 1772-1834 -- Correspondence; Critics -- Great Britain -- Correspondence